Pengaruh Kecerdasan Intelektual, Minat Belajar, dan Lingkungan Belajar Terhadap Tingkat Pemahaman Akuntansi - Moh Vicentcio Arya Lingga; Haposan Banjarnahor (LPPM Universitas Putera Batam, 2026)
This study is intended to evaluate and test the influence of intellectual intelligence, learning interests, and learning environment on the level of accounting understanding. This study uses quantitative data analysis. The number of students who became the population in this study was 1,347. The sampling method uses the Slovin formula with the number of respondents being 93 respondents. Data was collected through a Google Form-based questionnaire using the Likert scale measurement method. Data processing and analysis was carried out with the help of SPSS version 25. The results of the analysis show that each variable, intellectual intelligence has a significant influence on the level of accounting understanding. Interest in learning has no effect on the level of accounting understanding and the learning environment has a significant influence on the level of accounting understanding. Simultaneously, intellectual intelligence, learning interests, and learning environment have a significant influence on the level of accounting understanding.